Pengaruh Senam Kaki Diabetik terhadap Ankle Brachial Index (ABI) pada Pasien Diabetes Mellitus Tipe II di Puskesmas II Denpasar Selatan - I Made Lasia; I Gusti Ayu Ratih Agustini; Ni Komang Purwaningsih (Poltekkes Kemenkes Malang, 2020)
Diabetes mellitus is a degenerative disease with an increasing number of patients characterized by hyperglycemia due to impaired insulin secretion, insulin performance, or both. Ineffective management in treating DM will lead to complications such as Peripheral Arterial Disease which can progress to diabetic foot ulcers. One of the examinations which can be done to determine the condition of the lower limb blood vessels is the Ankle Brachial Index. Interpretation of ABI value can be used as an indicator of effective treatment for DM patients. One of the tertiary prevention is diabetic exercise. The purpose of this study was to determine the effect of diabetic foot exercise on Ankle Brachial Index of Patients with Diabetes Mellitus Type II in Public Health Center II South Denpasar. This research design used quasy experiment. The sampling technique used a formula for quasy experimental research with pre and posttest design with control group. A number of sample was 23 respondents in treatment group and 23 respondents in control one. The result of statistical test using Wilcoxon Sign Rank test and obtained p value 0,000. From these results it can be concluded that there was an influence of diabetic foot exercise on Ankle Brachial Index of Patients with Diabetes Mellitus Type II in Public Health Center II South Denpasar.